Digital Foundations Introduction to Media Design with the Adobe Creative Cloud - burrough, xtine; Mandiberg, Michael (Open textbook library., 2017)
Digital Foundations uses formal exercises of the Bauhaus to teach the Adobe Creative Suite. All students of digital design and production—whether learning in a classroom or on their own—need to understand the basic principles of design in order to implement them using current software. Far too often design is left out of books that teach software for the trade and academic markets. Consequently, the design software training exercise is often a lost opportunity for visual learning. This revised edition updates the original text for use with Adobe Creative Cloud 2017 software.